Efektivitas Metode Mendongeng (Storytelling) dalam Meningkatkan Keterampilan Berbicara dan Keterampilan Membaca Siswa (Sebuah Studi Kasus di SDN 55 Bengkulu Selatan) - David Budi Hidayat; Abdul Muktadir Muktadir; I Wayan Dharmayana (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2020)
This study aims to find out how much the storytelling method can improve speaking skills and student reading skills and to determine the effectiveness of using storytelling methods in students' speaking skills and reading skills. The population of this study were all students of SDN 55 Bengkulu Selatan. The sample used was 30 students in one class in class III SDN 55 South Bengkulu. This study was classified as quasi experimental with one group pretest posttest design which only used one group for the pretest and posttest design. The instrument of this study was a test, this initial study was conducted pretest, then carried out the application of the storytelling method (treatman) and the final activity was carried out posttest. The results of the study on speaking skills showed that there was an increase in student scores from 38 to 50.83, which included aspects of intonation 31.03%, pronunciation aspects 35.59%, fluency aspects 34.52%, and vocal aspects 33.94%. The results of the reading skills study showed that there was an increase in student scores from 40.66 to 51.83 which included 25.81% pronunciation aspects, 25.42% intonation, 33.32% fluency aspects, and 25.40% sound clarity aspects. This study concluded that: First, the Storytelling method can improve speaking skills and reading skills in students as indicated by an increase in the average score of 33.77%, for speaking skills and an increase in the average score of 27.48%, for reading skills, which covering each of the four aspects of speaking and reading. Second, the Storytelling method gives a significant influence (0.05) in improving students' speaking and reading skills. This study will contribute to teachers as one of the effective strategies in teaching students to speak and read.